التعليم الريادي و دوره في خلق المؤسسات الناشئة .دراسة حالة طلبة المسجلين لدى حاضنة الاعمال جامعة الوادي - سهام،بوعنان; قمر،عابد; بثينة،ونيسي; ايناس،بالطاهر (university of eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى ابراز دور التعليم الريادي في خلق المؤسسات الناشئة حيث تمحورت إشكالية هذه الدراسة حول: " ما مدى مساهمة التعليم الريادي و دوره في خلق المؤسسات الناشئة لدى الطلبة المسجلين في حاضنة الأعمال بالوادي ؟، ولتحقيق أهداف هذه الدراسة تم جمع البيانات من مصادر مختلفة، وقد اعتمدت الدراسة على المنهج الوصفي، حيث تم توزيع (100) استبيان على عينة من الطلبة المسجلين في حاضنة الأعمال جامعة الوادي وتم استرداد حوالي (86) استبيانه ، ولتحليل البيانات واختبار فرضيات الدراسة وتقدير النموذج القياسي تم استخدام الحزمة الإحصائية للعلوم الاجتماعية (25.SPSS V)، و تم التوصل إلى أن أبعاد التعليم الريادي المتمثلة في ( معرفة عالم المشاريع، مهارات انشاء وتأسيس المشاريع مهارات تسيير المشاريع، مهارات تطوير المشاريع ) لها أثر ايجابي في خلق المؤسسات الناشئة لدى الطلبة المسجلين في حاضنة الأعمال جامعة الوادي . This study aims to examine the impact of entrepreneurial education on the creation of start-ups، focusing specifically on students enrolled in the business incubator at the University of El Oued. The central research question addresses: "To what extent does entrepreneurial education contribute to the establishment of start-ups among these students?" To achieve the study's objectives، data were collected from various sources، employing a descriptive-analytical methodology. A total of 100 questionnaires were distributed to a sample of students in the business incubator، with 86 completed questionnaires returned. Data analysis، hypothesis testing، and model estimation were conducted using the Statistical Package for the Social Sciences (SPSS) version 25. The findings indicate that the dimensions of entrepreneurial education—comprising knowledge of the entrepreneurial ecosystem، skills in project creation and establishment، project management skills، and project development skills—positively influence the creation of start-ups among the students registered in the business incubator at the University of El Oued.
مذكرة ماستر ادارة اعمال
Keywords: تعليم الريادي، مؤسسات الناشئة، حاضنة الأعمال الجامعية، SPSS‏ Entrepreneurial education، start-ups، university business incubator، university of Eloued، business incubator